Insurers' investment strategies: Pro- or countercyclical? - Linda Rousová; Margherita Giuzio (European Central Bank (ECB), 2019)
Traditionally, insurers are seen as stabilisers of financial markets that act countercyclically by buying assets whose price falls. Recent studies challenge this view by providing empirical evidence of procyclicality. This paper sheds new light on the underlying reasons for these opposing views. Our model predicts procyclicality when prices fall due to increasing risk premia, and countercyclicality in response to rises in the risk-free rate. Using granular data on insurers' government bond holdings, we validate these predictions empirically. Our findings contribute to the current policy discussion on macroprudential measures beyond banking.
Keywords: G01; G11; G12; G22; G23; 330; insurance companies; cyclicality; portfolio allocation; financial stability; sovereign debt crisis